2019
DOI: 10.1111/pirs.12464
|View full text |Cite
|
Sign up to set email alerts
|

Why are some Spanish regions more resilient than others?

Abstract: Which of a region's characteristics most strongly influence its degree of resilience? This study constructs a composite resilience index for the Spanish regions and uses Multiple Factor Analysis to compare it with the Martin resilience index (Martin, 2012). The results of a Principal Components Analysis to measure the relative contributions of potential regional resilience drivers indicate that, during recovery periods, it is market-service focused regional economies that show stronger resilience, while, in cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 73 publications
1
27
0
2
Order By: Relevance
“…Although not wholly new to economics, resilience has recently become a popular topic of investigation in the field (Ubago Martínez et al 2019; Escribá-Pérez, Murgui-García, and Ruiz-Tamarit 2017). Resilience entered economic discourse only after being first studied in contexts of engineering, ecology, and psychology 1 (Martin and Sunley 2015), resulting in its three leading interpretations: engineering resilience, which is the ability of a region to bounce back from a shock; ecological resilience, which considers a change in growth patterns of regions after a shock (Martin 2012); and adaptive resilience, which considers differential trajectories of economic activity after a shock (Martin and Sunley 2015).…”
Section: Resilience Its Determinants and The Role Of Inequality: Thmentioning
confidence: 99%
See 3 more Smart Citations
“…Although not wholly new to economics, resilience has recently become a popular topic of investigation in the field (Ubago Martínez et al 2019; Escribá-Pérez, Murgui-García, and Ruiz-Tamarit 2017). Resilience entered economic discourse only after being first studied in contexts of engineering, ecology, and psychology 1 (Martin and Sunley 2015), resulting in its three leading interpretations: engineering resilience, which is the ability of a region to bounce back from a shock; ecological resilience, which considers a change in growth patterns of regions after a shock (Martin 2012); and adaptive resilience, which considers differential trajectories of economic activity after a shock (Martin and Sunley 2015).…”
Section: Resilience Its Determinants and The Role Of Inequality: Thmentioning
confidence: 99%
“…One of the issues in measuring resilience is the lack of a standard set of quantitative indicators (Ubago Martínez et al 2019). The use of employment outcomes to measure resilience is common in the economics literature (e.g., Fingleton et al 2012; Martin 2012; Kitsos and Bishop 2018; Rahe et al 2019).…”
Section: Resilience Its Determinants and The Role Of Inequality: Thmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, relevant studies have shown that labour conditions (Ríos, 2017) and human capital endowment (Lo Cascio, Mazzola, & Epifanio, 2018) represent an important determinant of different regional impact of the last great economic crisis (Ubago, García-Lautre, Iraizoz, & Pascual, 2019) and with profound, specific and complex reflection on key socio-economic regional phenomena.…”
mentioning
confidence: 99%